Interference and Its Consequences: An East Cree Variant of Deviance? - Preston, Richard J. (Anthropologica, 2022)
This paper contains a critique of the arbitrariness of Becker’s definition of social labelling. It is suggested that the process must be seen to involve a classification of actions on the basis of their perceived consequences within the community. Among the Eastern Cree preservation of community integrity is a paramount goal, and threats to that integrity should be dealt with in a non-violent way.